2021
DOI: 10.3390/ijms22105187
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System in Obesity and Insulin-Resistance—The Complex Interplay between Leptin and Central Nervous System

Abstract: The role of the autonomic nervous system in obesity and insulin-resistant conditions has been largely explored. However, the exact mechanisms involved in this relation have not been completely elucidated yet, since most of these mechanisms display a bi-directional effect. Insulin-resistance, for instance, can be caused by sympathetic activation, but, in turn, the associated hyperinsulinemia can activate the sympathetic branch of the autonomic nervous system. The picture is made even more complex by the implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…Consistent with these studies, we found that serum leptin levels had a significant correlation with FSI and HOMA-IR levels. Moreover, a growing body of data has suggested that elevated serum leptin levels may play a role in the increase in insulin resistance in obesity ( 27 ). Additionally, a partial reduction in plasma leptin levels can restore hypothalamic leptin sensitivity and effectively decrease weight gain as well as improve insulin sensitivity in obesity ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, we found that serum leptin levels had a significant correlation with FSI and HOMA-IR levels. Moreover, a growing body of data has suggested that elevated serum leptin levels may play a role in the increase in insulin resistance in obesity ( 27 ). Additionally, a partial reduction in plasma leptin levels can restore hypothalamic leptin sensitivity and effectively decrease weight gain as well as improve insulin sensitivity in obesity ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recall that FQs on their own have a significant negative impact on cardiac function [22][23][24]137]; whether the described cardiotoxicity is a result of this hypothesized sympathetic nervous system hyperactivation or an additional side effect, is still unknown. If, instead, FQs administration result in vagal downregulation due to blockade of GABA A receptors at the mNTS, we could expect a decrease in gastric emptying and pancreatic exocrine secretion which, as proposed in a recent paper by Russo and collaborators [166] could be causing weight loss. Interestingly, unexplained weight loss has been reported by floxed patients, and described in a clinical case by Golomb and collaborators [168].…”
Section: Discussionmentioning
confidence: 91%
“…With blockade of GABAA receptors by FQs possibly resulting in vagal hyperactivation, it is safe to assume that the fine balance between the sympathetic and parasympathetic nervous system would most likely be altered to favor the parasympathetic tone. However, physiological increases in insulin levels following carbohydrates consumption normally leads to an increase of glucose metabolism in dorsomedial hypothalamic neurons, which become ultimately activated and mediate an increase in sympathetic tone [165,166]. This mechanism has been extensively investigated in the context of obesity to explain the rise in sympathetic nervous system activation in obese individuals, and illustrates how insulin, while unable to exert its functions due to insulin resistance in obesity, can still act on the sympathetic nervous system in an excitatory fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is associated with potentiation of the sympathetic nervous system ( 27 ). Previously, clinical studies have identified an association between autonomic nervous system regulation and obesity ( 28 , 29 ). Notably, it has been shown that as body weight increases, baroreflex function is significantly suppressed ( 28 ).…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%